Game analysis of Liverpool football club in English premier league season 2019/2020 - A/L Magesvaran, Navin Kumar (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Success is linked to the ability to keep the ball in their possession and make more passes during soccer games. Many people have been impressed by Liverpool FC's dominance in the English Premier League (EPL) in recent years especially season 2019/2020. Objective: The purpose of this study was to compare Liverpool FC's performance to that of their opponents, and found out the key indicator is that Liverpool FC won the EPL 19/20 season. Methods: In this study, the Performance Indicators (P.I) were total shots (TS), shot on target (SOT), percentage of ball possession (BP), total touches (TT), total passes (TP), and goal scored (GS). Twelve matches from the 2019/2020 English Premier League (EPL) season were chosen. The official website of the English Premier League (EPL) provided data for 12 matches. The data was organized in Microsoft Excel sheets based on the P.I. An independent T-test was used to analyze the differences between the teams, and Spearman's rho correlation test was performed to determine the correlation between the P.I. Between Liverpool FC and their opponents. Results: There was a significant difference in the total shoot (p=0.012), shoot on target (p=0.022), ball possession, total touch, and total passes (p=0.000). Except for the goal scored, all variables had positive correlations between them. Conclusion: This study found that a high number of total touches and passes, as well as a high percentage of ball possessions, influence a team's ability to win a soccer game in England.